Method of reduction of data uncertainty in monitoring systems based on ontological additions - Kaplunov, A.V.; Volokyta, A.M. (Problems of Informatization and Management, 2023)
The proposal for the use of ontological additions has a perspective in the field of distributed systems monitoring, when there is uncertainty in the totality of the collected data, and it is quite difficult to obtain clear parameters by traditional measurement methods due to a number of objective reasons. It was proposed to present an ontologically supplemented set of collected information in the form of: S_O^+=⟨A,P,V,γ,ω,O⟩ where O is the ontology of the system. In this way, ontologies make it possible to carry out a logical analysis of monitoring objects and perform redefinition of their attributes, thereby increasing the amount of information in the totality of collected information. In addition, the prospect of creating ontological additions by automated means based on Data Mining analysis was considered. The article presents the results of a theoretical study of the possibilities of using the expanded set of collected information. The approach proposed in the study can play a significant role in expanding the capabilities of monitoring systems and improving their operational characteristics.